Absence of dopamine D4 receptors results in enhanced reactivity to unconditioned, but not conditioned, fear - Falzone, Tomas Luis (2002)
The prefrontal cortex receives a major dopaminergic input from the ventral tegmental area, which plays an important role in the integration of neuronal signals influencing behavioural responses to stressful environmental stimuli. The dopamine D4 receptor (D4R) is expressed at highest levels in the prefrontal cortex and is the predominant D2-like receptor localized in this brain area. To investigate the functional significance of D4Rs in dopamine-mediated responses we have analysed a strain of mice lacking this receptor subtype (Drd4-/-). Wild-type and Drd4-/- mice were challenged in two different approach/avoidance conflict paradigms: the elevated plus maze and the light/dark preference exploration test. By these behavioural measures Drd4-/- mice showed heightened avoidance to the more fear-provoking areas of each maze as demonstrated by reduced exploration of the open arms of the plus maze and longer latencies to explore the illuminated compartment of the light/dark shuttle box. These exaggerated avoidance behaviours were further enhanced by an additional handling stress but completely prevented by anxiolytic agents such as the benzodiazepine midazolam and ethanol. Although Drd4-/- mice displayed heightened anxiety, they exhibited normal ethanol preference and consumption in a two-bottle choice test. Learned fear responses evaluated by contextual, cued and instrumental fear-conditioning tests showed no difference between wild-type and Drd4-/- mice. Taken together these results indicate that the absence of D4Rs increases avoidance behaviour to unconditioned stimuli and does not impair behavioural reactions to Pavlovian fear-conditioning, suggesting that the D4R could play a key role in the dopaminergic modulation of cortical signals triggered by environmental stimuli.